Neutrophil‐to‐lymphocyte ratio as a predictor of clinical outcomes in critically ill COVID‐19 patients: A retrospective observational study. Issue 5 (15th September 2022) - Ali, Husain S.; Ananthegowda, Dore C.; Ebrahim, Ebrahim M. A.; Kannappilly, Nevin; Al Wraidat, Mohammad; Mohamed, Ahmed S.; Khatib, Mohamad Y.
Abstract: Background: Timely identification of patients at risk of worse clinical outcomes is vital in managing coronavirus disease 2019 (COVID‐19). The neutrophil‐to‐lymphocyte ratio (NLR) calculated from complete blood count can predict the degree of systemic inflammation and guide therapy accordingly. Hence, we did a study to investigate the role of NLR value on intensive care unit (ICU) admission in predicting clinical outcomes of critically ill COVID‐19 patients. Methods: We conducted a retrospective analysis of electronic health records of COVID‐19 patients admitted to ICUs at Hazm Mebaireek General Hospital, Qatar, from March 7, 2020 to July 18, 2020. Patients with an NLR equal to or higher than the cut‐off value derived from the receiver operating characteristic curve were compared to those with an NLR value below the cut‐off. The primary outcome studied was all‐cause ICU mortality. The secondary outcomes evaluated were the requirement of mechanical ventilation and ICU length of stay (LOS). Results: Five hundred and nineteen patients were admitted to ICUs with severe COVID‐19 infection during the study period. Overall, ICU mortality in the study population was 14.6% (76/519). NLR on ICU admission of ≥6.55 was obtained using Youden's index to predict ICU mortality, with a sensitivity of 81% and specificity of 41%. Mortality was significantly higher in patients with age ≥60 years ( p  < 0.001), chronic kidney disease ( p  = 0.03), malignancy ( p  < 0.002), and NLR ≥ 6.55 ( p  < 0.003). There was also a significant association between the requirement of mechanical ventilation (34.7% vs. 51.8%, p  < 0.001) and increased ICU LOS (8 vs. 10 days, p  < 0.01) in patients with ICU admission NLR ≥ 6.55. Conclusion: Higher NLR values on ICU admission are associated with worse clinical outcomes in critically ill COVID‐19 patients.